ASPECTS THAT INFLUENCE ADOLESCENT MENTAL HEALTH - Akbar, Resti; Anissa, Mutiara; Fitri, Amelia; Fitria, Annisa (Nusantara Hasana Journal, 2024)
Mental health is how a person adapts to themselves, others, and the environment. Adjusting to oneself is an effort to understand and accept one's strengths and weaknesses. The transition period from childhood to adulthood is called adolescence. According to the World Health Organization (WHO), adolescents are individuals aged 10 to 19 years, 80% of whom live in developing countries. Teenagers' emotional and mental well-being is related to the type of parenting they receive, whether it is authoritarian, permissive, or democratic. Adolescents who have a poor peer environment are in line with the increase in adolescents who experience mental and emotional problems. This is because teenagers do not get enough emotional support or social support from friends their age. Also, the living environment significantly impacts teenagers' lives, especially in character development. It can also endanger mental health if something terrible happens in the surrounding environment, creating a feeling of insecurity or discomfort about living in a slum area. The high use of social media can also influence adolescent behavior. Apart from that, it also has an indirect negative impact on mental health, such as the emergence of anti-social attitudes or, what is usually called apathy, and various other mental health disorders. So, several aspects can influence teenagers' mental health, one of which is parenting style, social environment, and internet addiction.